Спектр мутаций ядерного локуса DFNB1 у пациентов с несиндромальной СНТ, жителей Беларуси - Шубина-Олейник, О.А.; Синявская, М.Г.; Левая-Смоляк, А.М.; Меркулова, Е.П.; Даниленко, Н.Г. (Фактори експериментальної еволюції організмів, 2015)
Aims. The genetic nature of sensorineural hearing loss (SNHL) has so far been studied for many ethnic groups in various parts of the world. Among the different subtypes of autosomal recessive non-syndromic hearing impairment, DFNB1 locus is remarkable for its high frequency in most populations. Here we present the results of study of DFNB1 mutations among 391 young patients with non-syndromic SNHL in order to develop an algorithm of molecular genetic diagnosis of hearing loss for people in Belarus. Methods. The PCR-RFLP method was used for detection of three mutations: 35delG and IVS1+1G>A both in GJB2 gene as well as deletion del (GJB6-D13S1830) in DFNB1 locus. For analysis of the GJB2 coding exon SSCP followed by sequencing was carried out. Results. We have found that 35delG GJB2 mutation is the main cause of hearing defects in 391 Belarusian patients with SNHL. This point deletion has been detected in 53 % of the patients with SNHL. The 312del14 and IVS1+1G>A GJB2 were respectively the second and the third most frequent mutations in the Belarus patients cohort. Conclusions. Mutations in DFNB1 locus is the main reason of congenital non-syndromic hearing loss in Belarus: about 60 % of all SNHL cases connected to them. Based on the results obtained the recommendations for molecular genetic testing of the causes of non-syndromic hearing loss in Belarus were suggested.